AIDS and UK respiratory physicians: attitudes to confidentiality, infection control, and management. Issue 1 (January 1990) - Church, S; Owen, S; Woodcock, A A
Abstract : Respiratory physicians are concerned in the management of most patients with AIDS. Attitudes and practices of 463 respiratory physicians in the United Kingdom in relation to confidentiality, infection control, and treatment were sought by questionnaire from December 1987 to March 1988; 266 replies were received. Thirty eight per cent of respondents had not seen an HIV positive patient at the time of the survey. Respiratory physicians followed General Medical Council guidelines in relation to consent and confidentiality, except that if the patient's consent was withheld three quarters of the physicians would still inform an at risk hospital health care worker; only a quarter, however, would inform an at risk spouse. Routine infection control was frequently inadequate and "disease specific"--that is, substantially increased for known HIV positive patients. Given an HIV positive patient with respiratory symptoms and an abnormal chest radiograph, two thirds of respiratory physicians said that they would treat empirically for Pneumocystis carinii pneumonia as opposed to immediate bronchoscopy for accurate diagnosis. If a patient with AIDS who had pneumocystis pneumonia developed respiratory failure, half the physicians said at that time that they would elect not to ventilate the patient.